2016
DOI: 10.1371/journal.pone.0155457
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Methamphetamine Effects on Brain Structure and Function in Rats

Abstract: Methamphetamine (MA) addiction is a growing epidemic worldwide. Chronic MA use has been shown to lead to neurotoxicity in rodents and humans. Magnetic resonance imaging (MRI) studies in MA users have shown enlarged striatal volumes and positron emission tomography (PET) studies have shown decreased brain glucose metabolism (BGluM) in the striatum of detoxified MA users. The present study examines structural changes of the brain, observes microglial activation, and assesses changes in brain function, in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 71 publications
1
48
1
Order By: Relevance
“…The inability to quit taking methamphetamine is probably related to persistent neuroadaptive changes in brain regions thought to be responsible for rewarding effects of drugs and cognitive processes that regulate habitual behaviors23. These neuroadaptations are thought to include altered synaptic plasticity, transcriptional alterations, and epigenetic changes in mesostriatal and mesocorticolimbic projection areas such as the nucleus accumbens (NAc)456.…”
mentioning
confidence: 99%
“…The inability to quit taking methamphetamine is probably related to persistent neuroadaptive changes in brain regions thought to be responsible for rewarding effects of drugs and cognitive processes that regulate habitual behaviors23. These neuroadaptations are thought to include altered synaptic plasticity, transcriptional alterations, and epigenetic changes in mesostriatal and mesocorticolimbic projection areas such as the nucleus accumbens (NAc)456.…”
mentioning
confidence: 99%
“…Previously, we found that chronic MP, provided at doses that mimic the pharmacokinetic profile of treated patients, results in a myriad of effects on physiology (including skeletal development) (Komatsu et al 2012; Uddin et al 2018; Robison et al 2017b; Thanos et al 2015), behavior (Robison et al 2017b;Thanos et al 2015), and neurochemistry (Robison et al 2017a) in normal rats, with some effects persisting beyond the end of treatment. There is a concerning gap in knowledge, however, as to whether chronic MP treatment could result in significant brain inflammation, as has been shown following chronic administration of related psychostimulants (Cadet et al 2005; Thanos et al 2016a). …”
Section: Introductionmentioning
confidence: 99%
“…Due to an increase in cytokines and chemokines, excess dopamine has been shown to induce an inflammatory response in the brain, which could lead to an induction of microgliosis (Jang et al 2012). Therefore, one possible consequence of MP treatment that has not been fully explored is its ability to trigger inflammatory and neurodegenerative processes, as has been shown to result from chronic administration of related psychostimulants (Gonçalves et al 2010;Thanos et al 2016a;Cubells et al 1994; Cadet et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…METH is a widely-abused central nervous system (CNS) psychostimulant, which reduces hippocampal volume and induces apoptosis in the hippocampus in experimental animals and humans, particularly when administered at high doses [22,23,24,25,26]. METH also affects adult neurogenesis in the hippocampus [22,27,28].…”
Section: Introductionmentioning
confidence: 99%